Analisis Tingkat Partisipasi Olahraga dan Kebugaran Jasmani Masyarakat Kabupaten Pemalang Ditinjau dari Sport Development Index (Indonesian Journal for Physical Education and Sport, 2021)
This research was carried out because the level of community participation and community physical fitness in the development of sports in Pemalang district was not yet known. The research objective was to determine the level of community participation and community physical fitness in sports development in Pemalang district. The research method uses a survey. The sample in the research community who did sports activities was 90 people. The sampling technique used in this study was stratified random sampling. Data analysis in this study is a quantitative approach using the Sport Development Index analysis. The results of the research on the level of community participation in Pemalang Regency with an index of 0.22 were in the low category. The level of physical fitness of the Pemalang district community with an index of 0.02 is in the low category. The conclusion of this research is that the level of community participation in Pemalang Regency with an index of 0.22 is in the low category. The level of physical fitness of the Pemalang district community with an index of 0.02 is in the low category. Suggestions from researchers are 1) It is necessary to further increase public awareness in exercising 2) The government needs to increase programs that can change the people's mindset to exercise as well as adequate infrastructure and infrastructure for the general public in Pemalang Regency.